This or That? Perception of Filipino Generation Z and Generation Alpha in Using Common Emojis: Semantics and Typology - Tamaño, Lexxus Dominic (RADINKA JAYA UTAMA PUBLISHER, 2025)
Emojis have become integral to digital communication, functioning as visual cues that convey emotion, intent, and social meaning beyond literal text. Guided by Semiotic Theory, this research investigates generational differences in how Filipino Generation Z and Generation Alpha perceive and classify common emojis in terms of semantics and typology. A convergent parallel mixed methods design was employed, involving surveys and structured interviews with 16 students equally distributed between the two generations. Quantitative results from the Chi-Square Test of Independence indicated a statistically significant generational difference in emoji usage (χ² = 26.74, p < 0.05). Qualitative thematic analysis revealed that Gen Z frequently interprets emojis symbolically or sarcastically utilizing them to signal passive-aggression, express exaggerated humor, or convey disapproval. In contrast, Gen Alpha tends to assign more literal and emotionally transparent meanings to the same icons. Despite the limited sample size restricting broad generalizability, the findings demonstrate distinct generational patterns in digital expression. These differences suggest potential sources of miscommunication in online and educational environments. The study recommends the development of a digital literacy toolkit to foster generational awareness and promote clearer, more empathetic emoji-mediated communication.